Strategi Penguatan Calistung Siswa SD Jorong Duo Koto dalam Meningkatkan Mutu Pembelajaran - Sherin Afiqah; Davit Setiawan Saputra Laowo; Patriani Putri Umami; Annas Abdul Aziz; Nurli Putra; Esy Maestro (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This research aims to describe strategies for strengthening reading, writing and arithmetic (calistung) skills for lower class elementary school students in Jorong Duo Koto, Nagari Guguak Malalo. This activity was carried out in the context of Padang State University Real Work Lectures (KKN) in July–August 2025. The approach used was descriptive qualitative with data collection methods in the form of observation, interviews and documentation. The main strategy implemented includes providing Calistung tutoring outside of school in an informal but structured manner, with a fun and personal approach. The results of the activity showed that some students showed enthusiasm and progress in their calistung abilities. Even though there are obstacles such as limited learning media, low intrinsic motivation, and students' lack of pedagogical experience, adaptive and contextual learning strategies are able to make a positive contribution to improving the quality of basic learning in the area.